Entre las distorsiones de las guitarras eléctricas y el charango: Sónica, cuerpo y performance en las prácticas sonoro-musicales de los jóvenes músicos emberá chamí (Colombia). - Molano Zuluaga, Juan Carlos (2018)
This article is framed in the ethnomusicological interpretations deducted in my field work, in the Emberá Chamí indigenous resguardo in San Lorenzo; in this, the main objective was referring my work in an ethnography of the musical groups of indigenous youths. In this sense, this work evidences musical performance though a punk-rock event made in one of the most encumbered communities in San Lorenzo resguardo and it was denote certain political resistances, corporal and sonic behaviors in the territory. The intention is showing the socio-musical and socio-political meanings that these young musicians attribute to their sound-performance practices, privileging in this case, the tensions generated between: musicians, social actors, residents and the governors of the territory, by the sonic position that these young people attributes to their soundmusical practices.The Emberá Chamí indigenous youth are making different ways of fighting and resistance in order to their voices would be listening, they promulgate them with their sonorous performance practices. With these interpretations just concluding that the Emberá indigenous way of being / stay in San Lorenzo, is evidenced of through certain interpretations so that have been consolidated by the appropriation, listening and practice of punk-rock and Peruvian-Bolivian Andina music.